Correction to: Suspected paracetamol overdose in Monrovia, Liberia: a matched case-control Study - Mohamad K. Haidar; Florian Vogt; Islam Amine Larabi; Kensuke Takahashi; Fanny Henaff; Lisa Umphrey; Nikola Morton; Luke Bawo; Joseph Kerkula; Robin Ferner; Klaudia Porten; Jean-Claude Alvarez; et al. (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.